Role of the G-Protein-Coupled Receptor Signaling Pathway in Insecticide Resistance - Li, Ting (Int J Mol Sci, 2019)
The G-protein-coupled receptor (GPCR) regulated intracellular signaling pathway is known to be involved in the development of insecticide resistance in the mosquito, Culex quinquefasciatus. To elucidate the specific role of each effector in the GPCR regulating pathway, we initially expressed a GPCR, G-protein alpha subunit (Gαs), adenylate cyclase (AC), and protein kinase A (PKA) in insect Spodoptera frugiperda (Sf9) cells and investigated their regulation function on cyclic AMP (cAMP) production and PKA activity. GPCR, Gαs, and AC individually expressed Sf9 cells showed higher cAMP production as the expression of each effector increased. All the effector-expressed cell lines showed increased PKA activity however. Moreover, Sf9 cytochrome P450 gene expression and cell tolerance to permethrin were examined. The relative expression of CYP9A32gene in Sf9 cells tested was significantly increased in all effector-expressed cell lines compared to a control cell line; these effector-expressed cell lines also showed significantly higher tolerance to permethrin. Inhibitor treatments on each effector-expressed cell line revealed that Bupivacaine HCl and H89 2HCl robustly inhibited cAMP production and PKA activity, respectively, resulting in decreased tolerance to permethrin in all cell lines. The synergistic functions of Bupivacaine HCl and H89 2HCl with permethrin were further examined in Culex mosquito larvae, providing a valuable new information for mosquito control strategies.